GGBFS and Red-Mud based Alkali-Activated Concrete Beams: Flexural, Shear and Pull-Out Test Behavior - Hebah M. Al-Jabali; Ahmed A. El-Latief; Mohamed Salah Ezz; Shady Khairy; Amr A. Nada (Salehan Institute of Higher Education, 2024)
Geopolymers and antacid-enacted fasteners have accumulated critical interest as promising development and fixing materials because of their exceptional properties. Also, they bring about less contamination contrasted with regular concrete cements. Geopolymers address a clever class of suggested restricting materials blended through the basic enactment of bountiful aluminosilicate materials. The usage of geopolymer materials from side effects offers a critical decrease in carbon impression and yields positive natural effects. Geopolymer is progressively recognized as a plausible substitute for OPC concrete. In this review, sodium-based antacid activators, especially sodium metasilicate (Na2SiO3), were used for different blend extents. The boundaries researched included NaOH arrangements with a grouping of 8 M, alongside a Na2SiO3/NaOH proportion of 1. This paper evaluates the fundamental characteristics of geopolymer cement beams, employing red mud and GGBFS in powdered form as complete replacements for traditional concrete. Six bar specimens are tested under a two-point static loading condition, all cured at room temperature under ambient conditions. Of the six beams, three were exposed to flexural conduct testing with a molarity of 8 M, while the excess three beams were tried for shear conduct. The outcomes of testing geopolymer beams subjected to shear and bending loads indicated that the beams incorporating aluminum slag performed better than those incorporating blast furnace slag. Both types also demonstrated promising results compared to beams incorporating OPC, highlighting their potential environmental benefits compared to cement use. Doi: 10.28991/CEJ-2024-010-05-09 Full Text: PDF